2016
DOI: 10.3892/ol.2016.5037
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer patients exhibit increased levels of galanin in serum and colon tissues

Abstract: Galanin (GAL) is a 30-amino acid neuropeptide that is expressed in both the central and peripheral nervous system, including the enteric nervous system (ENS). Increased GAL concentrations have been identified in the blood of colorectal cancer (CRC) patients. The aim of the present study was to assess whether sections of the colon wall containing ENS plexuses or CRC tumor are associated with increased GAL concentrations. Blood samples were collected from 68 CRC patients and 39 healthy volunteers. In addition, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 31 publications
2
32
1
Order By: Relevance
“…They found significant reduction (by approximately 50%) of the area occupied by galanin-immunoreactive neurons in the MPs located in the vicinity of CRC invasion in comparison to distally located plexuses. The authors suggested that neither apoptosis nor necrosis has been involved in the observed phenomena [15,16]. These finding have been confirmed by the results of our ultrastructural study, which showed neither neurons' apoptosis nor necrosis to occur in myenteric plexuses located close to the CRC tumor.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…They found significant reduction (by approximately 50%) of the area occupied by galanin-immunoreactive neurons in the MPs located in the vicinity of CRC invasion in comparison to distally located plexuses. The authors suggested that neither apoptosis nor necrosis has been involved in the observed phenomena [15,16]. These finding have been confirmed by the results of our ultrastructural study, which showed neither neurons' apoptosis nor necrosis to occur in myenteric plexuses located close to the CRC tumor.…”
Section: Discussionsupporting
confidence: 80%
“…Our study presents an attempt to explain the observations by Kwiatkowski et al [15] and Kozlowska et al [16] who applied morphometry to measure the area of MPs close to and distant from CRC invasion. They found significant reduction (by approximately 50%) of the area occupied by galanin-immunoreactive neurons in the MPs located in the vicinity of CRC invasion in comparison to distally located plexuses.…”
Section: Discussionmentioning
confidence: 93%
“…Latest studies showed that ENS may undergo severe decomposition under various pathological conditions. For example, it was reported that MPs in the vicinity of the colorectal cancer (CRC) tissue were significantly smaller and had lower number of neurons per plexus compared to distally located plexuses [ 5 , 6 ]. Similar observations were also reported in the colon wall of patients with diabetes [ 7 ] and severe constipation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the ENS, this neuropeptide is hypothesized to influence the gastrointestinal motility (by inhibition of acetylcholine and substance P release from excitatory motor neurons) as well as secretion (through GAL 1 receptors—GAL-R 1 ) [ 14 ]. Elevated GAL levels in the serum and colon tissues were observed in patients with CRC [ 6 ]. Thus it has been proposed that an increase in number of GAL-immunoreactive (-IR) neurons can be associated with adaptive and neuroprotective possibilities of the enteric neurons that is well-documented in many experimental models of brain and neurons injury [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nerve damage within the large intestine has been observed during inflammatory diseases [ 23 , 24 ], as well as in colon cancer [ 25 ]. Moreover, in the case of the latter disease, the most visible changes concerned the expression of neuronal active substances in the ENS [ 26 , 27 , 28 , 29 ]. Previous studies showed that CART-LI in the enteric neurons may also be subject to such changes.…”
Section: Introductionmentioning
confidence: 99%